STUDY OF THE DIVERSITY OF THE ALGOFLORA OF THE IRTYSH RIVER AND ISOLATION OF NEW STRAINS OF PHOTOTROPHIC MICROORGANISMS - Shissenbayeva, N.; Sadvakasova , A.; Akmuhanova , N.; Sarsekeeva , F.; Bauenova , M.; Kanshora , A. (Eurasian Journal of Applied Biotechnology, 2023)
The article presents the results of studies of the diversity of the composition of the algoflora of the Irtysh River in the Pavlodar region.85 species of microalgae were detected in water samples from different points of the Irtysh River.According to the frequency of occurrence, the main part of it is made up of green and blue-green algae.Analysis of individual species of saprobic microalgae revealed the presence of 16 species of indicator microalgae of the Irtysh River.The saprobity index for bioindication analysis is 1.8 (β-mesosaprobic). According to the results of work on the extraction of pure cultures from samples taken from the Irtysh River, 5 algologically and bacteriologically pure cultures of microalgae were obtained: Oscillatoria tenuis A-1, Phormidium autumnale D-2, Anabaena Variabilis A - 2, Synechococcus elongatus D-6, Nostoc calcicola YAD-3 were isolated.